RELEVANSI AYAT-AYAT AL-QURAN TERHADAP PENGGUNAAN TEKNOLOGI MULTIMEDIA DALAM DAKWAH MULTIKULTURAL - Aslati M.Ag (Jurnal Dakwah Risalah, 2013)
Islamic teachings brought by the Prophet Muhammad SAW covers all aspects of the life embodied in the quran. There was the revelation of God that in the quran is not only applicble at the time when and where is the revelation the lower, however accurs at all ages. The verses of the quran in dakwah is able to answer the challenges of the times. Islam is the religion of dakwah for rahmatal lil ‘alamin allows believers to understand the techings contained in it bith in textual and contextual. Appeal of da’wah is contained in the quran allows his people to deliver amar ma’ruf nahy munkar indication through a variety of methods and media that can support the achievement of business objectives of teh dakwah. One method of dakwah in islam is to dakwah bit-tadwin. Enter the global times like today, a pattern of bit-tadwin propagation (dakwah through writing) good by publishing books, magazines, internet, newspaper. and writings containing the message propagation is very importand and effecttive. Im the dakwah that wear these methodsn in line with the word of the Prophet : “ actually, the religious expert’s ink is better than the blood of the syuhada”. The following description try to revisit how the relevance of the texts of Dakwah that is in the quran with a multicultural society a mid the media trend in the current global era.